(untitled) - R O'Neill (Oxford, 1996)
The book deals with eleven basic concepts of English dealt with at three different levels of difficulty. The situations and vocabulary deal with such topics as work and entertainment, and controversal themes such as marriage and politics.
Keywords: english language - study and teaching - foreign speakers